HEPATITIS: TYPE CHANGE, SYMPTOMS, DIAGNOSIS AND TREATMENT METHODS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Hepatitis is an inflammatory disease of the liver tissue that can occur for a variety of reasons. There are viral forms of hepatitis (A, B, C, D, E), as well as autoimmune, alcoholic and drug-dependent types. In this article, the etiology, pathogenesis, clinical manifestations, methods of diagnosis and treatment of hepatitis are widely covered on the basis of medical sources. The article also discusses the role of hygiene, vaccinations and healthy lifestyle in protecting against disease.